Space and the memories of violence : landscapes of erasure, disappearance and exception - Schindel, Estela 1968- HerausgeberIn; Colombo, Pamela 1983- HerausgeberIn (Palgrave Macmillan memory studies, 2014)
Introduction: the multi-layered memories of space / Pamela Colombo and Estela Schindel -- Spatial inscriptions of annihilation. Violent erasuresá and erasingá violence: contesting Cambodia's landscapes of violence / James A. Tyner -- Polish landscapes of memory at the sites of extermination: the politics of framing / Zuzanna Dziuban -- Spaces of confrontation and defeat: the spatial dispossession of the revolution in Tucuman, Argentina / Pamela Colombo -- Subterranean autopsies: exhumations of mass graves in contemporary Spain / Francisco Ferrandiz -- The representation of violence: spatial strategies. Faces, voices, and the shadow of catastrophe / Jay Winter -- Theatrical cartography of a space of exception / Juan Mayorga -- "The cartographer. Warsaw, 1:400.000" by Juan Mayorga in its first English translation / by Sarah Maitland -- "All limits were exceeded over there": the chronotopeof terror in modern warfare and testimony / Kirsten Mahlke -- The concentration camp and the "unhomely home": the disappearance of children in post-dicatorship Argentine theatre / Mariana Eva Perez -- Haunted spaces, irrupting memories. "The whole country is a monument": framing places of terror in postwar Germany / Aleida Assmann -- Haunted houses, horror literature and the space of memory in post-dictatorship Argentine literature / Silvana Mandolessi -- Counter-movement, space, and politics: how the Saturday mothers of Turkey make the enforced disappearances visible / Meltem Aahska -- An orderly landscape of remnants: notes for reflecting on the spatiality of the disappeared / Gabriel Gatti -- A boundless grave: memory and abjection of the Rio de la Plata / Estela Schindel -- Spaces of exception, power and resistance. Spatialities of exception / Pilar Calveiro -- Imaginary cities, violence and memory: a literary mapping / Gudrun Rath -- Occupied squares and the urban "state of exception": in, against and beyond the city of enclaves / Stavros Stavrides -- "Memory, that powerful political force": interview with David Harvey